An international clinical perspective on functioning and disability in adults with cerebral palsy. Issue 3 (July 2022) - Noten, Suzie; Rodby-Bousquet, Elisabet; Limsakul, Chonnanid; Tipchatyotin, Suttipong; Visser, Fay; Grootoonk, Anneke; Thorpe, Deborah E.; van der Slot, Wilma MA; Selb, Melissa; Roebroeck, Marij E.; ,; Roebroeck, Marij E.; et al.
Abstract: Background: This international, multi-center cross-sectional study is one of the preparatory studies in the development of the International Classification of Functioning, Disability and Health (ICF) Core Sets for adults with cerebral palsy (CP) to describe their functioning and health. Objective: To identify the most common problems in functioning of adults with CP presenting in healthcare services, and facilitating and hindering environmental factors, using the ICF as a reference. Methods: Participants were adults with CP who visited healthcare services in the Netherlands, Sweden, Thailand, and the United States. Structured interviews were performed using an adapted version of the generic ICF checklist 2.1a (106 categories) to rate the participant's functioning and the impact of environmental factors. Descriptive statistics were used for frequency analysis. Results: In total, 101 participants were included, of whom 69 without intellectual disability (mean age ± SD of 38.4 ± 14.7 y; 85.5% with spastic type of CP; Gross Motor Function Classification System (GMFCS) levels I–V) and 32 with intellectual disability (mean age ± SD of 25.0 ± 6.4 y; 71.9% with spastic type of CP; GMFCS levels I–V). A total of 104 ICF categories in the ICF checklist were frequently present in adults with CP: 27 body functions, 4 body structures, 53 activities and participation, and 20 environmental factors. Conclusions: The most common problems of adults with CP presenting in healthcare services are diverse and highly prevalent. The study results add the clinical perspective on relevant categories of functioning to the basis for developing the ICF Core Sets for adults with CP. Highlights: Adults with cerebral palsy in healthcare services indicate a broad range and a high frequency of specific functioning problems, facilitating and hindering factors. Difficulties in activities and participation were most frequently reported, especially in adults with intellectual disability. Environmental factors were more often mentioned as facilitators than as barriers.